The empress file - Camp, John, 1944-; Copyright Paperback Collection (Library of Congress) (New York : Berkley Books, 1991)
When fourteen-year-old Darrell Clark is mistakenly killed by local cops and the inevitable cover-up occurs, Marvel Atkins sets out to destroy the entire corrupt bureaucratic and political machine of Longstreet, Mississippi.
Keywords: Kidd (Fictitious character : Camp) -- Fiction; Political corruption -- Fiction; Swindlers and swindling -- Fiction; Mississippi -- Fiction; Adventure fiction; Mystery fiction